Systemic swings in end-Permian climate from Siberian Traps carbon and sulfur outgassing. Issue 12 (December 2018) - Black, Benjamin; Neely, Ryan; Lamarque, Jean-François; Elkins-Tanton, Linda; Kiehl, Jeffrey; Shields, Christine; Mills, Michael; Bardeen, Charles
Abstract Siberian Traps flood basalt magmatism coincided with the end-Permian mass extinction approximately 252 million years ago. Proposed links between magmatism and ecological catastrophe include global warming, global cooling, ozone depletion and changes in ocean chemistry. However, the critical combinations of environmental changes responsible for global mass extinction are undetermined. In particular, the combined and competing climate effects of sulfur and carbon outgassing remain to be quantified. Here we present results from global climate model simulations of flood basalt outgassing that account for sulfur chemistry and aerosol microphysics with coupled atmosphere and ocean circulation. We consider the effects of sulfur and carbon in isolation and in tandem. We find that coupling with the ocean strongly influences the climate response to prolonged flood basalt-scale outgassing. We suggest that sulfur and carbon emissions from the Siberian Traps combined to generate systemic swings in temperature, ocean circulation and hydrology within a longer-term trend towards a greenhouse world in the early Triassic. Carbon and sulfur release from the Siberian Traps igneous province caused climate swings during the end-Permian mass extinction, according to coupled global climate simulations.